Strategi Mempertahankan Loyalitas Kerja SDM dalam Meningkatkan Produktivitas Community Officer di PT. Bank BTPN Syariah Tbk. MMS Rantau Rasau - Penti Puspita Sari; Sry Rosita; Dian Mala Fithriani Aira (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
Work loyalty is a fundamental pillar in human resource management that plays a critical role in sustaining organizational development and enhancing employee productivity. This study aims to explore and analyze the strategies implemented by PT. Bank BTPN Syariah MMS Rantau Rasau in maintaining employee loyalty, particularly among Community Officers who serve as the frontline representatives of the bank in delivering services directly to local communities. The research adopts a descriptive qualitative approach using in-depth interviews and documentation as data collection techniques. The findings reveal that work loyalty can be fostered through several strategies, including equitable and measurable reward systems, regular and relevant training, structured career development, and appropriate compensation and performance-based incentives. Additionally, leadership support and effective two way communication between management and employees play a crucial role in cultivating a sense of ownership and emotional attachment to the organization. These strategies significantly contribute to strengthening employee commitment, dedication, and the willingness to stay and grow with the company, ultimately leading to increased productivity in both quantitative target achievement and qualitative service delivery. This study offers practical implications for the development of human resource management policies in the Islamic banking sector and serves as a reference for other organizations facing similar challenges in maintaining employee loyalty and improving productivity. A comprehensive understanding of loyalty strategies enables organizations to build a sustainable and productive work environment.